Copper-catalysed β-silylation of α,β-unsaturated esters under mild reaction conditions. - Siti Suhaila Sulaiman. (2010)
A highly-efficient β-silylation of α, β-unsaturated esters was developed, utilizing N-heterocyclic carbene copper(I) catalyst via a unique protocol based on Si ̶B activation. By employing MeOH as a basic additive which is necessary to promote the reaction, the β-silylation products can be readily obtained. All the reactions proceeded at room temperature with good yields. A mechanistic cycle has been proposed to account for the process.